2021
DOI: 10.1107/s2052252521007715
|View full text |Cite
|
Sign up to set email alerts
|

Chasing the structural diversity of the transcription regulator Mycobacterium tuberculosis HigA2

Abstract: Transcription factors are the primary regulators of gene expression and recognize specific DNA sequences under diverse physiological conditions. Although they are vital for many important cellular processes, it remains unclear when and how transcription factors and DNA interact. The antitoxin from a toxin–antitoxin system is an example of negative transcriptional autoregulation: during expression of the cognate toxin it is suppressed through binding to a specific DNA sequence. In the present study, the antitox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Based on previous studies, the antitoxin HigA2 in Mtb acts as a transcriptional regulator with self-cleavage and structural flexibility and may bind DNA through HTH motifs [ 17 ]. Our study found that HigA2 binds within the higB2 gene, and the expression of HigA2 in M. smegmatis resulted in growth inhibition of the bacteria, whereas the toxin HigB2 did not show toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous studies, the antitoxin HigA2 in Mtb acts as a transcriptional regulator with self-cleavage and structural flexibility and may bind DNA through HTH motifs [ 17 ]. Our study found that HigA2 binds within the higB2 gene, and the expression of HigA2 in M. smegmatis resulted in growth inhibition of the bacteria, whereas the toxin HigB2 did not show toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the HigBA2 system may play a key role in the formation of Mtb persisters. In addition, the protein crystal structure of HigA2 has been resolved and was found to have N-terminal autocleavage activity that spontaneously removes the N-terminal’s 30 amino acids [ 17 ]. Although the three-dimensional protein structure of HigA2 has been characterized, its DNA recognition site has not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…The clip structure, consisting of α3 and α4, is connected to the core domain by two flexible stretches that appear as coils. These segments likely confer the necessary flexibility for binding to the antitoxin [ 59 , 60 , 61 ].…”
Section: Focused Overviews On Structural and Functional Aspectsmentioning
confidence: 99%
“…The clip structure, consisting of α3 and α4, is connected to the core domain by two flexible stretches that appear as coils. These segments likely confer the necessary flexibility for binding to the antitoxin [59][60][61]. The VapBC5 complex adopts a hetero-tetrameric arrangement facilitated by a twofold axis within the crystallographic symmetry, thereby establishing a relationship between two hetero-dimeric units (Figure 1B).…”
Section: Vapbc5 Systemmentioning
confidence: 99%
“…Transcription factors (TFs) act as regulators of gene expression and possess the ability to identify distinct DNA sequences under various physiological circumstances [ 6 ]. They are extensively involved in the VC process.…”
Section: Introductionmentioning
confidence: 99%